STATUS TERUMBU KARANG DI PERAIRAN PESISIR NEGERI HUKURILA - Sahetapy, Dicky; Siahainenia, Laura; Selanno, Debby A J; Tetelepta, Johannes M S; Tuhumury, Novianty C (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2021)
Coral reef is one of the important coastal ecosystems that have high biodiversity. This study aims to analyze the composition of the taxa and the distribution of coral species, the ecological index of coral communities and the status of coral reefs. The research was conducted from April-May 2019 in the coastal waters of Hukurila Village, South Leitimur District, Ambon City. Collecting coral data by using the Line Intercept Transect (LIT) method. Determination of coral reef condition based on percent data (value) of coral reef cover. During the study, 116 species of stony coral from 49 genera and 16 families were found, which 50 species of them are protected and 23 species of ornamental coral. The similarity index of stony coral species between coral reef locations ranges from 0.52-0.76 or there is the similarity of stony coral species between locations coral reef in the amount of 52-76%. The coral reefs of Hukurila Village have high diversity of coral species, with a low dominance of coral species in the community, and the compatibility of coral species in the community is classified as stable. Acropora corals contributed a low covering percent value (9.98%), while Non-Acropora corals contributed a relatively high percent of covering value (43.56%). The status of coral reefs between locations in the coastal waters of Hukurila Village is in the criteria of good (healthy). ABSTRAK Terumbu karang merupakan salah satu ekosistem pesisir penting yang emiliki kenanekaragaman hayati tinggi. Penelitian ini bertujuan untuk menganalisis komposisi taksa dan sebaran spesies karang, indeks ekologi kominitas karang dan status terumbu karang. Penelitian dilakukan dari April-Mei 2019 di perairan pesisir Negeri Hukurila Kecamatan Leitimur Selatan Kota Ambon. Pengumpulan data karang menggunakan metode Line Intercept Transect (LIT). Penentuan kondisi terumbu karang berdasarkan data (nilai) persen penutupan karang batu. Selama penelitian ditemukan 116 spesies karang batu dari 49 genera dan 16 famili, dimana 50 spesies diantaranya dilindungi dan 23 spesies karang hias. Indeks similaritas spesies karang batu antar stasiun terumbu karang berkisar antara 0,52-0,76 atau terdapat kesamaan spesies karang batu antar lokasi terumbu karang sebesar 52-76%. Terumbu karang Negeri Hukurila memiliki diversitas spesies karang tinggi, dengan dominansi spesies karang rendah dalam komunitas, dan keserasian spesies karang dalam komunitas tergolong stabil. Karang Acropora memberi kontribusi nilai persen penutupan rendah (9,98%), sementara karang Non-Acropora memberi kontribusi nilai persen penutupan karang batu relatif tinggi (43,56%). Status terumbu karang antar stasiun terumbu perairan pesisir Negeri Hukurila berada dalam kriteria baik (sehat). Kata kunci: terumbu, karang batu, keragaman spesies, kesamaan, persen penutupan